Tumor microenvironment triggered biodegradation of inorganic nanoparticles for enhanced tumor theranostics. Issue 45 (16th July 2020) - Yang, Weitao; Yang, Suhong; Jiang, Liping; Zhou, Yujuan; Yang, Cuiling; Deng, Cuijun
Abstract : In this review, we summarize the recent advances in tumor microenvironment (TME)-triggered biodegradation of inorganic NPs accompanied by imaging signal amplification and the released ions-mediated tumor therapy. Abstract : Inorganic nanoparticles (NPs)-mediated tumor theranostics have attracted widespread attention due to their unique physicochemical properties, such as optical, electrical, magnetic, and thermal properties. In the past decade, great advancements have been made in inorganic NPs-associated drug delivery, multimodal tumor imaging, and tumor therapy. However, the potential toxicity of inorganic NPs due to their low biodegradability, background signals interference and treatment side effects limit their clinical application. Therefore, developing biodegradable and intelligent NPs is beneficial to avoid excessive metal ions deposition, specific tumor imaging and treatment. In this review, we summarize the recent advances in tumor microenvironment (TME)-triggered biodegradation of inorganic NPs accompanied by imaging signal amplification and the released ions-mediated tumor therapy. First, the feature characteristics of the TME are introduced, including mild acidity, hypoxia, overexpressed reactive oxygen species (ROS), glutathione (GSH), and enzymes et al. ; then, the biodegradation of NPs in a TME-induced activation of imaging signals, such as magnetic resonance (MR) imaging and fluorescence imaging is described; furthermore, tumor therapies through "Fenton", "Fenton-like" reactions, and interference of biological effects in cells is presented. Finally, the challenges and outlook for improving the degradation efficiency, imaging, specificity and efficiency of tumor imaging and treatment are discussed.